The relationship between serum lipid levels and colorectal serrated lesions: A systematic review and meta-analysis - Wang, Xuerui; Zou, Yangbin; Zhang, Ruxuan; Teng, Chunyan; Ren, Xuejiao; Zhang, Haishan; Zhou, Liting (Frontiers in Physiology, 2022)
Objective: To clarify the relationship between colorectal serrated lesions and serum lipid levels, and provide a scientific basis for the identification and early clinical prevention and treatment of populations that are at risk for colorectal serrated lesions. Methods: Studies comparing serum lipid levels in patients with colorectal serrated lesions and controls were searched in PubMed, Embase, Web of Science, the Cochrane Library, China Biomedical Literature Database, CNKI, Wanfang Database, and VIP Database. Relevant literature was screened according to the inclusion and exclusion criteria. The mean and standard deviation of the serum lipid levels in patients and controls were extracted from the included literature. The combined weighted mean difference (WMD) and 95% confidence intervals (CIs) were calculated using Review Manager 5.0 software to evaluate the relationship between serum lipid levels and colorectal serrated lesions. Publication bias of the included studies was evaluated by the Egger test. Results: Twenty-three studies were included, comprising 2,063 patients and 63,909 controls. The serum high-density lipoprotein cholesterol (HDL-C) levels in the case group was significantly lower than in the control group (WMD = −0.122 mmol/L, 95% CI: 0.170–0.073). Total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), and serum triglyceride levels in the case group were significantly higher than in the control group, and the WMDs were 0.180 mmol/L (95% CI: 0.061–0.299), 0.155 mmol/L (95% CI: 0.038–0.273), and 0.241 mmol/L (95% CI: 0.181–0.302), respectively. Conclusion: Colorectal serrated lesions may be related to blood lipid levels. Hyperlipidemia might be a risk factor for colorectal serrated lesions.